A review of related empirical research on retail payments - Zinman, Jonathan (Henry Stewart Talks, 2010)
Policy motivation: systemic risk, efficiency, monetary policy and forensics, Competition, Key policy questions, Are retail payments 2-sided markets?, Key parameters in 2-sided models, Consumer choice, Typical theory setup and implications, Elasticities, 'Behavioral' theories, Decision making, Future directions, Implications for policy, regulation and oversight